Estudo químico e biológico de espécies vegetais da família Boraginaceae (Gêneros Heliotropium e Tournefortia) - Medina, Janaina de Castro Marchi (2006)
Heliotropium transalpinum var. transalpinum Vell, popularly known as "Borragembranca", Heliotropium procumbens Mill, "Borragem-cinzenta" e Tournefortia paniculata Cham, "Marmelinho", are plants species belonging to Boraginaceae family and native from Paraná's river bordering forest, Paraná state - Brazil. In this section, the H. transalpinum var. transalpnum leaves are topically employed as wound healing and the leaf tea of T. paniculata is used on folk medicine as kidney anti-inflammatory and against diarrhea. There was no report about components isolation and the evaluation of biological or pharmacological activities of H. transalpinum var. transalpinum and H. procumbens. In this context, we had made the phytochemical investigation of H. transalpinum var. transalpinum and H. procumbens, which on the first species the triterpenes β-sitosterol and α-D-glucopiranosyl-sitosterol was separated and identified and six saturated pyrrolizidine alkaloids: 1β-2β-epoxy-1α-hydroximethyl-8α- pyrrolizidine (1) (subulacine), 1α-2α-epoxy-1β-hydroximethyl-8α-pyrrolizidine (47), 1β-2β- epoxy-1α-hydroximethyl-8α-pyrrolizidine N-oxide (48) (subulacine N-oxide) e 1β-2β- dihydroxi-1α-hydroximethyl-8α-pyrrolizidine (49 ). About the alkaloids, 48 and 49 are unpublished. The alkaloid 1 have the isolation already been reported from other specie of Heliotropium genus and alkaloid 47 is reported like product of organic synthesis along with 1. We also describe with CG-MS experiments a methylic fatty esters series. From H. procumbens was separated a triterpene compound, identified like β-sitosterol and stigmasterol, and two fatty esters series was characterized by CG-MS one of them holding within amine groups. A comparison by CG-MS of the T. paniculata components had been made with those known in H. transalpinum var. transalpinum. The biological activities evaluated was: a) anti-inflammatory - pleurisy model in Wistar rats, b) anti-inflammatory -oil-induced ear edema in Swiss mice, c) antiviral screening - virus Herpes simplex type 1 (HSI-1), d) antiproliferative for colorectal human cancer (HCT-116) and e) Artemia salina Leach. lethality assays. The results of anti-inflammatory, on pleurisy model, and antiviral (HSV-1) evaluations did not exhibit expressive values. The H. transalpinum var. transalpinum and H. procumnbens crude extracts showed significant antiproliferative activity but the isolated alkaloids did not. Artemia salina lethality assays were expressive for all H. transalpinum var. transalpinum extracts and fractions. The hexanic and ethyl acetate fractions showed the best lethality and these could be associated a bactericidal evaluation made previously that exhibited better bactericidal activities and bacterial inhibition on these fractions. On the ethanolic and alkaloidal extract of H. transalpinum var. transalpinum and on the ethanolic extract of H. procumbens the edema inhibitory effect had significative values, respectively 31%, 41% e 24%. All the H. transalpinum var. transalpinum fractions showed expressive edema inhibitory effect but these results were less significant than those presented to crude extract, indicating there were synergic effects within fraction components. The edema inhibitory effect, topical anti-inflammatory activity model, and antibacterial activity proved ethnopharmacology importance and support the local utilization of the species as wound healing.